Development of optimum friction new nano hybrid composite liner for biodiesel fuel engine. (August 2016) - Tiruvenkadam, N.; Thyla, P.R.; Senthilkumar, M.; Bharathiraja, M.
Highlights: Influencing factors of nano hybrid composite for friction coefficient were found. Optimum tensile and friction behaviors, a new cylinder liner material was developed. Developed liner increased biodiesel energy use in engine. Developed liner reduced CO, HC, and smoke emissions. Abstract: This work presents the preparation of aluminum (Al) 6061 nano hybrid composite samples reinforced with equal weight percentage of nano-ZrO2, micro-SiC, micro-Gr particles of 0%, 0.75%, 1.5%, 2.25%, and 3% using stir casting method. Friction characteristics of the composite samples under reciprocating conditions were studied at 125 °C using L27 orthogonal array and Taguchi method. The results of analysis of variance showed the influencing parameter for friction coefficient in the order of applied load and reciprocating sliding speed, followed by sliding distance and percent reinforcement. Hence, the total combined reinforcement sample of 6.75% was found to be optimum in terms of frictional characteristics and tensile strength. It was selected to synthesize lightweight nano hybrid composite cylinder liner (NL) and to replace the present cast iron cylinder liner (CL) used in biodiesel engine application. The developed NL had a 43.75% reduced weight than the currently used CL. Neat diesel and biodiesel from Jatropha oil and its diesel blends were used as test fuels. Experimental results proved that NL improved brake thermal efficiency, in-cylinder pressure, heat release rate and reduced carbon monoxide, hydrocarbon, and smoke emission in comparison with the existing liner. The results also showed that emission of the oxides of nitrogen (NO x ) increased marginally with the new liner. Thus, the newly developed NL was found suitable for both diesel- and biodiesel-operated internal combustion engines.